Bias Kognitif Dan Literasi Keuangan Pada Keputusan Investasi Generasi Z - Garnia, Erna; Mayesya, Yusevin Rossa; Lisaumi, Siti Riyyan (LPPM POLITEKNIK LP3I BANDUNG, 2026)
The rapid growth of the Indonesian capital market has been accompanied by increasing participation of Generation Z investors. However, investment decisions are not always rational as they are influenced by cognitive biases such as overconfidence and availability bias, as well as the level of financial literacy. Despite their digital nativity, Generation Z investors remain susceptible to psychological biases that may lead to suboptimal investment outcomes. This study aims to analyze the effect of overconfidence and availability bias on investment decisions with financial literacy as a control variable among Generation Z investors at Investment Galleries of universities in the Bandung Raya area. The research employed a quantitative approach with a verificative analysis design. Data were collected through questionnaires from 98 respondents and analyzed using multiple linear regression. The results indicate that overconfidence and availability bias significantly influence investment decisions, even when financial literacy is controlled. The findings confirm that psychological biases continue to affect the investment behavior of Generation Z, highlighting the need for comprehensive investment education that emphasizes both financial literacy enhancement and cognitive bias management strategies.